2017
DOI: 10.1007/978-94-024-1079-2_35
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Energy Production Contributes to Development of Failure in Taurine Deficient Heart

Abstract: Taurine forms a conjugate in the mitochondria with a uridine residue in the wobble position of tRNA. The resulting product, 5-taurinomethyluridine tRNA, increases the interaction between the UUG codon and AAU anticodon of tRNA, thereby improving the decoding of the UUG codon. We have shown that the protein most affected by the taurine conjugation product is ND6, which is a subunit of complex I of the respiratory chain. Thus, taurine deficiency exhibits reduced respiratory chain function. Based on these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…An estimated 70% of total body taurine is localized to muscles and plays vital roles in mitochondrial, muscular, and cardiovascular functions [26]. Deficiency of taurine has been linked to impaired mitochondrial energy production and decreased exercise performance and can result in cardiomyopathy [27]. In patients with Barth syndrome, plasma taurine was reported to be 36% lower than age-matched control values ( p = 0.07) [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 70% of total body taurine is localized to muscles and plays vital roles in mitochondrial, muscular, and cardiovascular functions [26]. Deficiency of taurine has been linked to impaired mitochondrial energy production and decreased exercise performance and can result in cardiomyopathy [27]. In patients with Barth syndrome, plasma taurine was reported to be 36% lower than age-matched control values ( p = 0.07) [9].…”
Section: Resultsmentioning
confidence: 99%
“…Taurine is a non-proteogenic amino acid that is considered essential for bioenergetics and has been shown to be integral for heart and skeletal muscle physiology [26]. Deficiency in taurine is associated with the pathological development of a dilated cardiomyopathy [27], providing rationale for the use of taurine supplementation for patients with congestive heart failure [45]. Plasma taurine was reported to be depressed by roughly 40% in Barth syndrome compared to age-matched controls [9].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Taurine deficiency increases the NADH/ NAD ratio and affects energy metabolism. 21,22 PCr, a fast and high-energy phosphate molecule, is essential for intracellular energy transfer systems. 23 When the ATP in the body is lacking, PCr will be decomposed into the ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine has been implicated in the maintenance of normal contractile function, modulation of myocardial calcium homeostasis, and potentially acts as an antioxidant and anti-inflammatory agent ( 123 , 128 ). Schaffer et al demonstrated that the taurine-deficient heart is associated with reduced ATP generation and is energy starved, possibly due to impaired mitochondrial respiratory chain activity, and NADH utilization ( 129 ). Although taurine deficiency causes reversible cardiomyopathy in cats ( 130 ), it does not play a significant role in the development of cardiomyopathy in dogs ( 91 ).…”
Section: Amino Acid Metabolismsmentioning
confidence: 99%